f(x) = 1-f(x-1) For positive integer x, if f(2)=12, then compute f(2006).

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

f(x) = 1-f(x-1) For positive integer x, if f(2)=12, then compute f(2006).

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

Oh god lol
oops that x=2 one sec
\[f(2)=1-f(2-1)=1-f(1)=12=> f(1)=-11\]

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

\[f(3)=1-f(2)=1-12=-11\] \[f(4)=1-f(3)=1-(-11)=12\] \[f(5)=1-f(4)=1-12=-11\]
Thank you! But what about f(2006)? I'm confused on how to incorporate that..
i think there may be a pattern
I see..
\[f(6)=1-f(5)=1-(-11)=12\] \[f(7)=1-f(6)=1-12=-11\]
see its either -11 or 12
all odds are -11 evens are 12
right
Wow, thanks so much you guys! First time using this site and I love it already. (:

Not the answer you are looking for?

Search for more explanations.

Ask your own question